Preventive effect of indomethacin and melatonin on 7, 12-dimethybenz/a/anthracene-induced mammary carcinogenesis in female Sprague-Dawley rats. A preliminary report - M ciková-Kalická, K; Bojková, B; Adámeková, E; Mníchová-Chamilová, M; Kubatka, P; Ahlersová, E; Ahlers, I (Folia biologica, 2001)
The aim of the experiment was to analyse the oncostatic effect of nonsteroidal antiinflammatory drug INDO, hormone MEL and combination of both substances in DMBA-induced mammary carcinogenesis in female SD rats. Chemoprevention started 10 days before the application of the first dose of DMBA to 35-day-old rats. INDO was administered in tap water (20 microg/ml of water) for 3 days in a week (days 2, 4 and 6), MEL solution in the concentration of 20 microg/ml of tap water was administered between 3 p.m. and 8 a.m. for 4 days in a week (days 1, 3, 5 and 7); during other days the animals drank tap water only. In combined chemoprevention, rats were drinking solutions of INDO and MEL according to the above-mentioned scheme. DMBA in the dose of 10 mg/rat was administered intragastrically using a probe to all rats 3 times on postnatal days 45, 50 and 55. There were four experimental groups: group 1--without chemoprevention, group 2--INDO treatment, group 3 --MEL treatment, group 4--application of INDO + MEL. The experiment lasted 26 weeks from the first administration of DMBA, when the final incidence and frequency of tumours per animal and group, as well as latency and average volume of tumours were evaluated. The content/concentration of malondialdehyde (MDA) was determined in selected tissues as a criterion of lipoperoxidation, considering its potential influencing by chemoprevention. The tumour incidence in controls was 100%; INDO reduced the incidence (36.84%) and frequency per group and animal, decreased the mean volume of tumours and prolonged the latency. Chemoprevention using combination of INDO with MEL was successful like that with INDO; however, it did not influence the tumour volume. MEL decreased the incidence to 42.11% and pronouncedly reduced the tumour frequency per group. INDO, administered alone or in combination with MEL, reduced an increased content/concentration of MDA in the liver, bone marrow and serum of tumour-bearing rats. INDO, MEL and INDO + MEL had a pronounced chemopreventive effect and showed to be a favourable combination in prevention of experimental mammary carcinogenesis.
Keywords: experimentální nádory mléčných žláz; potkani Sprague-Dawley; Anticarcinogenic Agents; Mammary Neoplasms, Experimental; 9,10-Dimethyl-1,2-benzanthracene; Indomethacin; melatonin; 9,10-dimethyl-1,2-benzanthracen; Melatonin; krysa rodu Rattus; Animals; ženské pohlaví; Carcinogens; karcinogeny; zvířata; Rats; indomethacin; Female; Rats, Sprague-Dawley; antikarcinogenní látky